2006
DOI: 10.5642/aliso.20062201.04
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Monocots Based on the Highly Informative Plastid Gene ndhF

Abstract: We used ndhF sequence variation to reconstruct relationships across 282 taxa representing 78 monocot families and all 12 orders. The resulting tree is highly resolved and places commelinids sister to Asparagales, with both sister to Liliales-Pandanales in the strict consensus; Pandanales are sister to Dioscoreales in the bootstrap majority-rule tree, just above Petrosaviales. Acorales are sister to all other monocots, with Alismatales sister to all but Acorales. Relationships among the four major clades of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
89
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 34 publications
13
89
1
3
Order By: Relevance
“…and even some Iridaceae . Similarly, Behniaceae, Blandfordiaceae, Ruscaceae, Tecophilaeaceae, and some Agavaceae (e.g., Hosta) possess net-veined leaves that are associated with mesic, forest-understory environments (see Givnish et al 2006 on concerted evolution of net-veined leaves and fleshy fruits in monocots). Given these morphological parallelisms, it can often be difficult to assign macromorphological characters to separate two families for taxonomic keys, as illustrated by African taxa of Anthericaceae and Asphodelaceae (Stedje and Nordal 1994).…”
Section: Morphological Synapomorphies and Parallelisms In Aspar-mentioning
confidence: 99%
See 3 more Smart Citations
“…and even some Iridaceae . Similarly, Behniaceae, Blandfordiaceae, Ruscaceae, Tecophilaeaceae, and some Agavaceae (e.g., Hosta) possess net-veined leaves that are associated with mesic, forest-understory environments (see Givnish et al 2006 on concerted evolution of net-veined leaves and fleshy fruits in monocots). Given these morphological parallelisms, it can often be difficult to assign macromorphological characters to separate two families for taxonomic keys, as illustrated by African taxa of Anthericaceae and Asphodelaceae (Stedje and Nordal 1994).…”
Section: Morphological Synapomorphies and Parallelisms In Aspar-mentioning
confidence: 99%
“…Polyploidization and chromosomal rearrangements are thought to generate reproductive isolation or prevent recombination in linkage groups that contain ecologically important loci, thereby playing a role in speciation (Riese berg 2001 ; Lonnig and Saedler 2002). Fluctuations in chromosome number and genome size have also been correlated with a number of morphological and environmental variables in plants, which can generate novel phenotypes that lead to habitat divergence (Levin 1983;Bennett 1987;Grime 1998;Ohri et al 1998;Watanabe et al 1999;Bennett et al 2000;Givnish et al 2000;Gregory 2002;Osborn et al 2003).…”
Section: Phylogenomics Of Asparagales: Necessity and Criteria For Devmentioning
confidence: 99%
See 2 more Smart Citations
“…Marker Genera/species of Bromeliaceae Ranker et al (1990) Givnish et al (1990 Clark and Clegg (1990) Clark et al (1993 restriction sites (cp) restriction sites (cp) rbcL rbcL rbcL 9/10 (T: 4/5, P: 3/3, B: 2/2) 7/7 3/3 7/7 7/7 (T: 3/3, P: 2/2, B: 2/2) Terry and Brown (1996) Givnish et al (1997) Terry et al (1997a) Terry et al (1997b) Horres et al (2000) ndhF restriction sites (nr ϩ cp) ndhF ndhF trnL intron 30/51 (T: 7/28, P: 8/8, B: 15/15) 4/19 (mostly Brocchinia; P: 4/19) 29/30 (T: 6/7, P: 8/8, B: 15/15) 9/28 (mostly Tillandsioideae) 32/62 (T: 7/23, P: 9/19, B: 16/20) Behnke et al (2000) Crayn et al (2000) rbcL matK 11/11 (T: 2/2, P: 5/5, B: 4/4) 15/40 (mostly Pitcairnioideae; T: 3/3, P: 11/36, B: 1/1) Reinert et al (2003) matK 11/35 (analysis of data by Crayn et al 2000, P: 11/35) Crayn et al (2004) Givnish et al (2005) matK & rps16 intron ndhF 24/51 (T: 7/10, P: 9/33, B: 8/8) 25/35 (T: 5/5, P: 14/24, B: 6/6) ter to a branch with Poaceae, Anarthriaceae, Restionaceae, Flagellariaceae, Xyridaceae, Cyperaceae, Juncaceae, Thurniaceae, and Mayacaceae (Chase et al 2000). In a study of ndhF cpDNA data analysis, Givnish et al (2006) found that members of Typhaceae are sister to Bromeliaceae at the base of the order Poales sensu APG II (2003), with Rapateaceae next divergent.…”
Section: Authors Molecular Datamentioning
confidence: 99%